Antibiotic Susceptibility of Bacteria Isolated From Under Nails - Zahraa AL-Taee1, Sura Ihsan Abed Jabuk1, Raflaa S.H. Hussian1, Zainab H. Kareem2, Yasir H. AL-Mawlah (Institute of Medico-legal Publications Pvt Ltd, 2020)
This study was designed for isolation and diagnosis of bacteria from under long dinger nails of a wide population of student (kindergarten, primary schools, elementary schools and university students) and study the antibiotic sensitivity for isolated bacteria. From 100 sample the bacterial isolate were Staphylococcus sp.(56 isolate), Bacillus sp.(1 isolate), Streptococcus sp. (1 isolate), Escherichia coli (40 isolate), Salmonella (2 isolate), Enterobacter(10 isolate), Klebsiella (10 isolate), Serratia (5 isolate) and Pseudomonad (6 isolate). The most effected antibiotic on all types of bacteria isolated from under the long nail was Gatifloxacin and the lowest effect was Cefazolin antibiotic. The concept of the study was isolating and determining bacteria, found under the long fingernails and studying their antibiotic sensitivity.